Self-Assembling Polymers with p-Aminosalicylate Anions Supported by Encapsulation of p-Aminosalicylate for the Improvement of Drug Content and Release Efficiency - Shadi Keihankhadiv; Dorota Neugebauer (MDPI AG, 2023)
Bioactive linear choline-based copolymers were developed as micellar carriers for drug delivery systems (DDSs). The polymethacrylates containing trimethylammonium groups with p-aminosalicylate anions (PAS-based copolymers: series 1) or chloride anions (Cl-based copolymers: series 2) differing in ionic content and chain length were selected for drug loading. The diverse structures of amphiphilic copolymers made it possible to adjust the encapsulation efficiency of a well-known antibiotic, i.e., p-aminosalicylate in the form of sodium salt (PASNa) or acid (PASA), providing single drug systems. Goniometry was applied to verify the self-assembly capacity of the copolymers using the critical micelle concentration (CMC = 0.03-0.18 mg/mL) and the hydrophilicity level quantifying the surface wettability of polymer film using the water contact angle (WCA = 30-53°). Both parameters were regulated by the copolymer composition, indicating that the increase in ionic content caused higher CMC and lower WCA, but the latter was also modified to a less hydrophilic surface by drug encapsulation. The drug content (DC) in the PAS-based polymers was increased twice by encapsulation of PASNa and PASA (47-96% and 86-104%), whereas in the chloride-based polymer systems, the drug was loaded in 43-96% and 73-100%, respectively. Efficient drug release was detected for PASNa (80-100% series 1; 50-100% series 2) and PASA as complete in both series. The strategy of loading extra drug by encapsulation, which enhances the drug content in the copolymers containing anions of the same pharmaceutics, provided promising characteristics, which highlight the potential of PAS-loaded micellar copolymers for drug delivery.